Studies in Oxidation of Gallic Acid with Potassium Dichromate - B. Chowdhury, R.; Bharti, V.D. (Asian Journal of Chemistry, 2010)
Oxidation of gallic acid with K2Cr2O7 has been investigated. The present paper deals with the characterisation of product obtained during the oxidation in solid state. The analytical and spectral study of the oxidation product indicates that it a trinucIear complex of Cr(III) containing OH– and O2– bridge and pyruvate ion ligand. The potentiometric titration in aqueous solution was also carried out. A tentative mechanism of the reaction is proposed on the basis of results.